Evaluation of anatomy courses in the faculty of dentistry in line with the views of academic staff and exam performance of students - Canbolat, Mustafa; Tatar, Numan (Annals of Medical Research, 2021)
Aim: Basic medical sciences have an important place in the curriculum of faculties of dentistry, just as in all fields of science dealing with health. One of these is anatomy. In the Faculty of Dentistry at İnönü University, anatomy course is taught in parallel with the Faculty of Medicine. The aim of this study is to compare the exam performances of medical faculty and dentistry faculty students since the curriculum of anatomy course at İnönü University is taught by the same faculty members and also to learn the attitudes of instructors at the faculty of dentistry through a questionnaire. Material and Methods: First, we compared the success rates of faculty of medicine and faculty of dentistry second year students in their anatomy practice exams during the academic years 2016-2017, 2017-2018 and 2018-2019. After, we conducted a study in which we asked the students to define anatomic structures on radiological images at the end of the academic year 2018-2019 when anatomy courses ended in both faculties. In the final stage of the study, we conducted a questionnaire for the instructors to get their opinions about the anatomy courses they received during their undergraduate education. Results: In all but one of the end of the board exams which were conducted during the three academic years, the success percentage of dentistry faculty students were found to be lower than those of medical faculty students. In the study in which we asked about the anatomic structures through radiological images, the number of the correct answers given by dentistry faculty students was lower than the number of correct answers given by medical faculty students. We believe that the success rate of dentistry faculty students were low since they lost their interest in the course because they were learning information they thought they would not need all their lives long. 73.91% of the instructors think that they received anatomy education more than they needed for their profession, which supports our opinion. Conclusion: We believe that it is wrong to follow the exact medical faculty curriculum in dentistry faculty for anatomy course.